Unilateral Acute Serous Retinal Detachment with Pachychoroid Following Postpartum Haemorrhage: A Case Report - Meduri, Enrico; Malclès, Ariane; Thumann, Gabriele; Bravetti, Giorgio Enrico (Klinische Monatsblätter für Augenheilkunde, 2025)
Purpose To elucidate the development and resolution of a unilateral acute serous retinal detachment (SRD) in a healthy patient following a complicated postpartum haemorrhage. This underscores the impact of systemic volume alterations and stress-induced factors on retinal fluid balance.Background Postpartum SRD is observed in individuals with pre-eclampsia and patients with previously diagnosed central serous chorioretinopathy, both attributed to hormonal and volumetric fluctuations during pregnancy.Case Description A 33-year-old woman presented with metamorphopsia and blurry vision in her left eye 24 hours following childbirth complicated by haemorrhagic shock. Notably, the patient had pre-delivery physiological vital signs with no alterations of consciousness, arterial blood pressure, or renal function. At presentation, the visual acuity in the left eye was 1.0 decimals and the anterior segment was within normal limits, while fundoscopy revealed a slight alteration in the foveal reflex. Spectral-domain optical coherence tomography (SD-OCT) revealed the presence of a dome-shaped SRD in the foveal region with a central foveal thickness of 279 µm and pachychoroid at 410 µm retro-foveally. The examination of the right eye and SD-OCT were unremarkable, except for the presence of pachychoroid at 367 µm retro-foveally. No treatment was initiated. At 48 hours, SD-OCT scans revealed complete resorption of the SRD in the left eye with a persistent focal alteration in the foveal region of the ellipsoid zone. Retro-foveal choroid thickness (RCT) was unchanged. At one month, visual acuity remained stable, and the patient was no longer symptomatic. The left eye SD-OCT revealed a reduction in CFT (279 µm vs. 224 µm, a 20.2% reduction) and RCT (410 µm vs. 360 µm, a 14.6% reduction) compared to baseline. Remarkably, the right eye also exhibited a 14.9% reduction in RCT (367 µm vs. 309 µm).Conclusion This case highlights the role that postpartum systemic changes and complications can play in the occurrence of retinal and choroidal changes. We believe that in this specific case, the development of acute SRD was probably due to oncotic fluctuations related to the hypovolaemic status following postpartum haemorrhage. This also emphasises the utility of SD-OCT for assessment and follow-up monitoring, providing valuable insights into retinal and choroidal changes over time.
Keywords: retina; pachychoroid; pregnancy; subretinal fluid; retinal vascular disease; OCT